Restrição maternal de tiamina afeta aspectos cognitivos espaciais e níveis cerebrais de GABA e glutamato da prole, avaliados em fases posteriores do desenvolvimento - Danielle Marra de Freitas Silva (2010)
Thiamine (vitamin B1) deficiency causes lesions in different brain regions and may affect glutamatergic and GABAergic circuits of the central nervous system, which are related to a range of behavioral aspects. Several studies on cognitive and biochemical changes in adult rats subjected to thiamine deficiency have been published; however, few studies address this issue using animals that underwent deficiency during the early stages of development. Thus, in the present study, we evaluated the effects of thiamine restriction during lactation (Part I) or peri-natal period (Part II) on spatial cognitive performance and cerebral levels of glutamate and GABA in the offspring. In both designs, evaluations were conducted in the young (age = 30 days) and adult stage (age = 75 days). Behavioral parameters were assessed for thirteen days using a test of spatial navigation, the Morris Water Maze. At the end of the tests, rats were decapitated and the levels of glutamate and GABA present in the thalamus, hippocampus and prefrontal cortex (PFC) were determined by High Performance Liquid Chromatography (HPLC). For this purpose, a chromatographic method for determination of the two amino acids was developed in the present work. Thiamine restriction during lactation (Part I) does not affect the relationship between encephalic weight and body weight in either young or adult rats. Although spatial learning was not affected by thiamine restriction during lactation, the speed of learning of young rats was significantly altered [F(1,27) = 5,91; p = 0,022]. None of the behavioral aspects - spatial learning and memory - evaluated in adults were affected. The concentrations of glutamate in the three brain regions examined [thalamus: F(1,26) = 37,98; p = 0,0001; hippocampus: F(1,26) = 13,35; p = 0,001; PFC: F(1,26) = 12,74; p = 0,001] and those of GABA in the thalamus [F(1,26) = 11,38; p = 0,002] of adult rats were significantly decreased by thiamine restriction. However, no significant differences in levels of these neurotransmitters were observed in young rats. When thiamine restriction was carried out in the peri-natal period (Part II) there was a significant effect of treatment on the relationship of encephalic weight and body weight of young animals [F(1,15) = 9,00; p = 0,009]. All young animals were able to learn the spatial navigation task, but the acquisition speed was affected by treatment [F(1,15) = 4,56; p = 0,049]. The relationship between encephalic/body weight and behavioral aspects was not affected at adulthood by the thiamine restriction during the perinatal period. This treatment did not affect the levels of glutamate and GABA in any of the brain regions analyzed in young and adult rats. The data obtained in this study show for the first time that maternal thiamine restriction can lead to cognitive and neurochemical changes in the offspring, indicating the importance of thiamine during pregnancy and lactation processes. Changes in the concentration of this vitamin during early periods of development can affect the neurobiology and behavior of the offspring. Although the studies on the effects of thiamine restriction during lactation or during the perinatal period were independent, preliminary observations of the effects of these treatments on biochemical parameters allow us to suppose that maternal thiamine restriction during lactation (Part I) causes stronger effects in the offspring than restriction in the perinatal period (Part II). Both restrictions during lactation and during the peri-natal period cause deficits in spatial learning in the offspring evaluated at the juvenile stage. A factorial study considering these two independent variables and a control of the recovery period should be conducted in the future.